2^2 + 4^2 + .. + (2n) ^2 = 2n(n+1)(2n+1)/3
平方和n(n+1)(2n+1)/6
推导:(n+1)^3-n^3=3n^2+3n+1
n^3-(n-1)^3=3(n-1)^2+3(n-1)+1
3^3-2^3=3*(2^2)+3*2+1
2^3-1^3=3*(1^2)+3*1+1.
把这n个等式两端分别相加,得:
(n+1)^3-1=3(1^2+2^2+3^2+.+n^2)+3(1+2+3+...+n)+n
由于1+2+3+...+n=(n+1)n/2
代人上式得:
n^3+3n^2+3n=3(1^2+2^2+3^2+.+n^2)+3(n+1)n/2+n
整理后得:
1^2+2^2+3^2+.+n^2=n(n+1)(2n+1)/6
a^2+b^2=a(a+b)+b(a-b)
奇数项:(2n-1)^2=4n^2-4n+1
S奇数=4(1^2+……+n^2)-4(1+……+n)+n
=4*n(n+1)(2n+1)/6-4*(1+n)n/2+n
=(2n+1)(2n-1)n/3
偶数项:(2n)^2=4n^2
S偶数=4(1^2+……+n^2)=2n(n+1)(2n+1)/3
立方和[n(n+1)/2]^2
推导:(n+1)^4-n^4=[(n+1)^2+n^2][(n+1)^2-n^2]
=(2n^2+2n+1)(2n+1)
=4n^3+6n^2+4n+1
所以有
2^4-1^4=4*1^3+6*1^2+4*1+1
3^4-2^4=4*2^3+6*2^2+4*2+1
4^4-3^4=4*3^3+6*3^2+4*3+1
(n+1)^4-n^4=4*n^3+6*n^2+4*n+1
各式相加有
(n+1)^4-1=4*(1^3+2^3+3^3...+n^3)+6*(1^2+2^2+...+n^2)+4*(1+2+3+...+n)+n
4*(1^3+2^3+3^3+...+n^3)=(n+1)^4-1+6*[n(n+1)(2n+1)/6]+4*[(1+n)n/2]+n
=[n(n+1)]^2
1^3+2^3+...+n^3=[n(n+1)/2]^2
奇数项:(2n-1)^3=8n^3-12n^2+6n-1
S奇数=8(1^3+……+n^3)-12(1^2+……+n^2)+6(1+……+n)-n
=8*[n(n+1)/2]^2-12*n(n+1)(2n+1)/6+6